Fluoxetine Ameliorates Atopic Dermatitis-Like Skin Lesions in BALB/c Mice through Reducing Psychological Stress and Inflammatory Response - Li, Yanxi; Chen, Long; Du, Yehong; Huang, Daochao; Han, Huili; Dong, Zhifang (Frontiers in Pharmacology, 2016)
Atopic dermatitis (AD) is a common chronic inflammatory skin disorder, and patients with AD suffer from severe psychological stress, which markedly increases the prevalence rate of depression and anxiety disorders in later life. Fluoxetine, a selective serotonin reuptake inhibitor, has recently been reported to exert anti-inflammatory and immunosuppressive effects. However, it is unclear whether fluoxetine is effective in the treatment of AD through reducing psychological stress and inflammatory reaction. Here, we reported that a BALB/c mouse model of AD was induced by application of 2,4‑dinitrochlorobenzene (DNCB) onto hairless dorsal skin. Chronic fluoxetine treatment (10 mg/kg per day, i.p.) significantly attenuated AD-like symptoms, as reflected by a dramatic decrease in scratching bouts, as well as a decrease in anxiety- and depressive-like behaviors. Furthermore, these behavioral changes were accompanied by a significant decrease in epidermal thickness, the number of mast cells in skin tissue, mRNA levels of interleukin-4 (IL-4) and IL-13 in the spleen, as well as serum immunoglobulin E (IgE) in the DNCB-treated mice by treatment with fluoxetine. Taken together, these results indicate that fluoxetine may suppress psychological stress and inflammatory response during AD development, and subsequently ameliorate AD symptoms, suggesting that fluoxetine may be a potential therapeutic agent against AD in clinic.